2021
DOI: 10.3390/drones5010004
|View full text |Cite
|
Sign up to set email alerts
|

Automated Agave Detection and Counting Using a Convolutional Neural Network and Unmanned Aerial Systems

Abstract: We present an automatic agave detection method for counting plants based on aerial data from a UAV (Unmanned Aerial Vehicle). Our objective is to autonomously count the number of agave plants in an area to aid management of the yield. An orthomosaic is obtained from agave plantations, which is then used to create a database. This database is in turn used to train a Convolutional Neural Network (CNN). The proposed method is based on computer image processing, and the CNN increases the detection performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Estimation of the agave area also improved with the deep learning algorithms; the estimation error was less than 40 m² when compared with the estimate obtained in the field (Table 1). The algorithm with the best overall precision and the lowest error in estimating agave area was OBIA, with an overall precision of 0.96, which is slightly better than that reported by Calvario et al (2020) andFlores et al (2021) for the detection of blue agave. The deep learning algorithms used in this study have the advantage that during the classification process they start from a distribution-free assumption; that is, no underlying model is assumed for the multivariate distribution of class-specific data in the feature space.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Estimation of the agave area also improved with the deep learning algorithms; the estimation error was less than 40 m² when compared with the estimate obtained in the field (Table 1). The algorithm with the best overall precision and the lowest error in estimating agave area was OBIA, with an overall precision of 0.96, which is slightly better than that reported by Calvario et al (2020) andFlores et al (2021) for the detection of blue agave. The deep learning algorithms used in this study have the advantage that during the classification process they start from a distribution-free assumption; that is, no underlying model is assumed for the multivariate distribution of class-specific data in the feature space.…”
Section: Resultsmentioning
confidence: 67%
“…They found that the estimate of the number of plants identified automatically in the images had an overall precision between 0.830 and 0.980. Another recent study, also carried out with blue agave, was Flores et al (2021). They applied a convolutional neural network (CNN), in which patterns and textures are learned, and used to carry out automated counts in images taken from UAVs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent FCN applications are the classification of tree species based on high resolution UAV images with less than 1.6 cm ground sampling distance (GSD) [11]. For specific tasks such as the detection and counting of agave trees in plantations, CNN are able to reach F1-scores of 96% [12]. These tasks are also accomplished by directly segmenting 3D-point clouds with 3D-CNN [13].…”
Section: Related Researchmentioning
confidence: 99%
“…They observed that the accuracy of the algorithm was affected by variability in plant size in the field and lighting conditions, obtaining a range of accuracy from 83 to 98 %. Furthermore, Flores et al (2021) created a database of agave plant images and performed automatic plant detection and counting using a CNN applied to RGB images captured by RPAS at an altitude of 50 m, achieving an accuracy of 96 %, but with a high computational cost. According to the review, the trend to implement DL techniques on sets of images acquired by RPAS in agriculture is reaffirmed.…”
Section: Introductionmentioning
confidence: 99%